Optimizing Oil Production at the Gathering Station by Maintaining the Oil Stock Tank / Interface Level in the Wash Tank Using the ROC System - Melysa, Rycha (UIR PRESS, 2021)
One of the production problems that arise at the Gathering Station is an unstable production problem, this is caused by controlling the level of fluid in the wash tank that is less than the maximum for that need to be improved by changing the system from manual to automatic. To maintain the stability of production at the gathering station, special measures such as controlling fluid levels in the storage tanks need to be carried out, monitoring pressure, temperature monitoring and so on that can have a positive effect on oil production at the gathering station. Wash Tank is a tank that is useful for temporary storage of liquid fluid (liquid) that comes from the boot gas. The liquid fluid entering the wash tank consists of a mixture of crude oil and water. At the Wash tank the process of separation between crude oil and water. This washing tank is the largest tank compared to other processing tanks at the gathering station, its diameter is around 85 ft to 90 ft, and its height is around 35 ft to 40 ft. The normal level in the separation process is 36 ft, where the level 1 ft - 29 ft is the water level, while the level 29 ft - 36 ft is the oil level. The 1ft - 29 ft level is referred to as the interface level, where the water level is expected to be at level 29 and the thickness of the oil / oil stock tank 7 ft in the wash tank. Research conducted on the problem of controlling the level of fluid in the wash tank, where manual control is ineffective and inefficient, for this reason it is necessary to change from a manual to automatic process with the ROC (Remote Operation Control) system, the changes made are expected to maintain the interface and the oil stock tank in accordance with the set point that has been determined and where the amount of oil production per day at the gathering station is very influential on the oil stock tank so that the oil pumped to the shipping line has a BS&W below 1% and has a temperature of 130 ° F -150 ° F In order to obtain this value, we must maintain the interface and the oil stock tank in accordance with the specified set point and where the amount of oil production per day at the gathering station is very influential on the oil stock tank